DNA fingerprint and diversity in aromatic rice by Gn1 gene linked SSR markers - Haque, MS; Tabassum, T; Saha, NR; Islam, MS (Progressive Agriculture, 2019)
Number of grains per panicle is a limiting factor for the yield of aromatic rice. Toovercome this limitation, itmight behelpful to screenaromatic rice using markers linked to grain number.In this study, an elementary DNA fingerprinting database of the nine aromatic rice cultivars was built using four SSR primer pairs linked to Gn1 gene responsible for grain number in rice. For genotyping of aromatic rice cultivars, DNA was extracted from leaf samples using IRRI standard protocol. Allele scoring was done by using a computer based program Alpha Ease FC 4.0 and data were analyzed by Power Marker version 3.25 software. Nei’s genetic distance value and similarity werecomputed. From the analysis, it was found that a total of 21 alleles were detected with an average number of 5.25 alleles per locus having PIC values ranging from 0.3402 (RM5493) to 0.7883 (RM3452) and the average value 0.6629. The highest gene diversity (0.8148) was observed in loci RM3452,and the lowest gene diversity (0.3404) was observed in loci RM5493.From the study, it can be stated that all of the aromatic rice germplasm have bands of the gene that influence the grain but they showed genetic variability.Information obtained from genotyping of varieties helped to analyze the genetic diversity within and among closely related crop varieties which has the potential for crop improvement and to meet the diverse goals like producing cultivars with increased yield of aromatic rice. Progressive Agriculture 29 (4): 336-344, 2018